High Rate of Multidrug‐Resistant Gram‐Negative Bacilli Carriage and Infection in Hospitalized Returning Travelers: A Cross‐Sectional Cohort Study. Issue 5 (22nd May 2015) - Epelboin, Loïc; Robert, Jérôme; Tsyrina‐Kouyoumdjian, Ellina; Laouira, Sonia; Meyssonnier, Vanina; Caumes, Eric; The MDR‐GNB Travel Working Group
<x xml:space="preserve">Abstract</x> Background Carriage of and infection with multidrug‐resistant Gram‐negative bacilli (MDR‐GNB) are a potential cause of concern in travelers with no history of hospitalization abroad. Methods All consecutive returning travelers hospitalized in our department between February 2012 and January 2013 were prospectively screened for MDR‐GNB gastrointestinal tract carriage or infection. We compared the prevalence of MDR‐GNB in travelers to a non‐travelers nonexposed group. Then among the travelers, MDR‐GNB carriers were compared to noncarriers to determine risk factors of acquisition of MDR‐GNB. Results Overall, 359 patients (191 travelers, 168 non‐travelers) were included, and 25 (6.4%), including 23 travelers, harbored MDR‐GNB. Five travelers had an MDR‐GNB infection while 18 were asymptomatic enteric carriers. MDR‐GNB carriage or infection was significantly more frequent in travelers (11.0% vs 1.2% for non‐travelers, odds ratio (OR) = 11.3, p < 0.001) and in patients born outside France (OR = 1.67; p = 0.03). Among travelers, in multivariate analysis, factors independently associated with MDR‐GNB carriage or infection were traveling to Asia (OR = 3.1; p = 0.01) and visiting friends and relatives (VFR) or migrants (OR=3.6; p = 0.01). Conclusions The 10‐fold higher prevalence rate of MDR‐GNB in travelers raises the issues of systematic screening of all travelers, and of the choice of first line antibiotic therapy when treating urinary tract infections in travelers, especially those VFR, migrants, and those returning from Asia.